Reflections on the role of chemical osmosis mechanisms on the long-term behavior of a collapsed salt cavity - Ledoux, Emmanuel; Hertz, Emmanuel; Robinet, Jean-Charles; Combes, Pierre (Comptes Rendus. Géoscience)
This article focuses on the mechanisms likely to generate salt flux towards the aquifer environment from a cavity created by dissolution within a layer of salt under clay cover, until causing its collapse. This problem is encountered by salt operators, particularly in Lorraine, who exploit a salt deposit located about 200 m deep isolated from an overlying aquifer by an argillaceous layer 130 m thick.The phenomenon usually invoked to quantify a potential salt emission is the molecular diffusion along the chimney filled by disturbed materials, which are put in place above the cavity following its collapse. Recent work on chemical osmosis in clay media, motivated by research on the geological storage of nuclear waste in a clay layer, raises questions about the role of this mechanism on the long-term behavior of the system.Based on a bibliographical approach, the article presents a brisk synthesis of the theory of chemical osmosis and discusses its application to the case of clayey rocks which can constitute imperfect membranes capable of generating osmotic pressures.First, the article presents the equations representing the flow of the fluid and the solute transport according to a simplified formulation adapted to the geometry of the system. It then proposes a set of plausible parameters making it possible to carry out a steady-state modeling of the transfers along the collapsed chimney by means of a numerical resolution in finite differences. Under the conditions representative of the exploitation of the Lorraine salt deposit, the results indicate that, depending on the case, overpressures or downward flows of fresh water may appear. A brine and dissolved salt balance is established and proves to be highly dependent on the osmotic efficiency coefficient, a parameter that is difficult to assess in natural environments. However, the fluxes remain low, indicating that the chemical osmotic effect is unlikely to significantly modify the orders of magnitude of the salt fluxes evacuated into the environment following intensive exploitation of a salt layer altering the protective clay series.